2020
DOI: 10.3390/en13123042
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Supply of Renewable Electricity to Metropolitan Regions in China

Abstract: The accelerated urbanization and industrialization in China is leading to major challenges due to rising energy demand and emissions. Cities in particular play an important role in the decision-making and implementation processes for the energy transition. However, they often have only limited local energy potential and are heavily dependent on supply regions. We therefore assess how a predominantly renewable power supply can be implemented based on the availability of local or imported renewable resources. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This large power demand is a special challenge. Recent studies have shown that the regionally integrated deployment of renewable technologies can technically manage this transition, even for the eastern demand centres [25,26]. Because of its industrial lifestyle, North America already has a high proportion of electrification and a large power demand.…”
Section: Regional Differencesmentioning
confidence: 99%
“…This large power demand is a special challenge. Recent studies have shown that the regionally integrated deployment of renewable technologies can technically manage this transition, even for the eastern demand centres [25,26]. Because of its industrial lifestyle, North America already has a high proportion of electrification and a large power demand.…”
Section: Regional Differencesmentioning
confidence: 99%
“…Different types of energy system models exist based on the particular modeling approach, scope, methodology and the level of spatial and temporal details considered [2,10,12]. Energy sector stakeholders such as policy makers, system operators, utilities and investors rely on the results of energy system models to formulate energy-related goals, economic and policy decisions, as well as to plan and operate the energy system [3,11,19]. Because of their high relevance for and impact on current and future energy policies as well as operating and planning decisions, it is important to interpret and assess outcomes of various energy system models and understand their discrepancies.…”
Section: Introductionmentioning
confidence: 99%